Parametric Study on Separation Performance of a New Downhole Sand Retrieval Device - Wang, Hao; Ye, Zhewei; Liu, Bing; Li, Changjiang (Scientific Journal of Technology, 2026)
The paper addresses the conditions of oil and gas wells with high sand content, low formation pressure coefficients, and high loss rates, where existing sand removal methods are inefficient. A novel sand-bailing device that is both fast and efficient has been designed. Its innovation lies in the design of a separation hood structure for sand and water separation within the cylinder, which enables direct and rapid sand removal. This paper investigates the various parameters affecting the separation efficiency of the novel sand-bailing device under transient conditions using computational fluid dynamics (CFD) methods, specifically employing the Euler model and the standard k-ε turbulence model. The simulation results were validated by comparing them with experimental results, confirming the accuracy and reliability of the simulations. The results indicate that the parameters affecting the separation efficiency of the device include the length of the inlet pipe, the diameter of the separation hood, the drilling speed, the inlet flow rate, the drilling fluid viscosity, and the sand particle size, and that the extent of their impact on the device’s separation efficiency varies. The research findings provide valuable theoretical guidance for the structural design and separation performance study of the novel sand-bailing device.